Systemic and Pulmonary Vascular Remodelling in Chronic Obstructive Pulmonary Disease. - Mariana Muñoz-Esquerre; Marta López-Sánchez; Ignacio Escobar; Daniel Huertas; Rosa Penín; María Molina-Molina; Frederic Manresa; Jordi Dorca; Salud Santos (PLoS ONE, 2016)
Chronic Obstructive Pulmonary Disease (COPD) is associated with subclinical systemic atherosclerosis and pulmonary vascular remodelling characterized by intimal hyperplasia and luminal narrowing. We aimed to determine differences in the intimal thickening of systemic and pulmonary arteries in COPD subjects and smokers. Secondary aims include comparisons with a non-smokers group; determining the clinical variables associated with systemic and pulmonary intimal thickening, and the correlations between systemic and pulmonary remodelling changes.All consecutive subjects undergoing lung resection were included and divided into 3 groups: 1) COPD, 2) smokers, and 3) non-smokers. Sections of the 5th intercostal artery and muscular pulmonary arteries were measured by histo-morphometry. Four parameters of intimal thickening were evaluated: 1) percentage of intimal area (%IA), 2) percentage of luminal narrowing, 3) intimal thickness index, and 4) intima-to-media ratio.In the adjusted analysis, the systemic arteries of COPD subjects showed greater intimal thickening (%IA) than those of smokers (15.6±1.5% vs. 14.2±1.6%, p = 0.038). In the pulmonary arteries, significant differences were observed for %IA between the 2 groups (37.3±2.2% vs. 29.3±2.3%, p = 0.016). Among clinical factors, metabolic syndrome, gender and COPD status were associated with the systemic intimal thickening, while only COPD status was associated with pulmonary intimal thickening. A correlation between the %IA of the systemic and pulmonary arteries was observed (Spearman's rho = 0.46, p = 0.008).Greater intimal thickening in systemic and pulmonary arteries is observed in COPD patients than in smokers. There is a correlation between systemic and pulmonary vascular remodelling in the overall population.